Adopting the OEE Method in the Air Separation Plant (ASP) Machine to Measure Its Productivity at PT XYZ - Niami, Khasbi; Romadlon, Fauzan (Jurnal Informasi, Sains dan Teknologi, 2024)
PT XYZ is a company that produces various gases in the form of Oxygen, Nitrogen, and Argon in gas and liquid form. In the production process, the machine runs 24 hours non-stop and will stop production when maintenance is employed once a year. The Air Separation Plant (ASP) machine performance measurements are needed to determine the effectiveness of its production. The reseacrh aims to analyze the factors that affect machine productivity. The method used is quantitative, using the Overall Equipment Effectiveness (OEE) approach. In addition, this study uses interviews to determine the factors that affect engine performance. The results show that the OEE value of the machine is 75%, which is still below the international standard OEE value of 85%. Therefore, it is necessary to optimize engine performance. Based on the analysis using a fishbone diagram, there are five influencing factors: human factors, machines, work methods, environment, and materials. Based on these five factors, the engine factor most influences the low value of engine performance. The predictive maintenance calculations are conducted, especially on expender and cold box machines, every 95 days of machine should use with work efficiency of around 40 hours.